Examining the Role of Relative Age on Leadership Behaviours among Female Ice Hockey Players: An Exploratory Investigation - Chittle, Laura; Horton, Sean; Dixon, Jess C. (Journal of Amateur Sport, 2020)
The aim of this study was to examine the influence of relative age on self-reported leadership behaviors among competitive female ice hockey players. Secondary purposes included examining whether a relative age effect (RAE) was present within the sample and if leadership behaviors differed according to leader status (i.e., formal versus informal leaders). Canadian female ice hockey players (ages 15-18 years) completed an online survey that contained the Leadership Scale for Sport along with additional demographic questions. Players were segmented into birth quartiles based upon Hockey Canada’s selection date and classified by leadership status. The MANOVA suggested that the frequency of leadership behaviors displayed by these athletes did not differ across birth quartiles. Furthermore, although there was a RAE trend within this sample of competitive female ice hockey players, the differences relative to population distributions were not statistically significant. Finally, formal leaders (i.e., captains/alternate captains) reported higher levels of social support, positive feedback, democratic behavior, and training and instruction than informal leaders. It appears that relative age is not a discriminating factor with respect to leadership behaviors. Competitive female ice hockey may be an avenue for all players, regardless of their date of birth, to develop and demonstrate leadership.